Smart Wearable Technologies for Real-Time Health Monitoring - Farhan Idris Jameel; Ahsan Taufiq Sharif (Proceeding of the International Conferences on Engineering Sciences, 2025)
Smart wearable technologies are becoming essential tools for real-time health monitoring, offering a new dimension of personalized medicine. Wearable devices equipped with biosensors, artificial intelligence, and Internet of Things (IoT) connectivity can continuously track vital signs such as heart rate, blood pressure, oxygen levels, and even detect early symptoms of diseases. This paper explores the latest advancements in wearable health technology, including flexible electronics, energy-efficient data processing, and integration with telemedicine platforms. Additionally, ethical concerns such as data privacy, cybersecurity risks, and user adoption challenges are discussed. The study provides insights into how smart wearables can be effectively utilized for preventive healthcare, chronic disease management, and real-time health diagnostics.